5G core network cloud-network integration operation ＆ maintenance - Xue ZHANG (Dianxin kexue)
Most operators in the world have turned to 5G independent networking architecture and have begun commercial deployment of 5G independent networking architecture.The 5G core network adopts NFV technology, which forms a variety of virtual resources for general computing, storage, and network hardware to achieve dynamic and flexible deployment of network functions and resources based on needs.With large-scale commercial deployment of 5G core network with network function virtualization technology, the operation ＆amp; maintenance of 5G core network is also facing new challenges.The difficulties of operation ＆amp; maintenance brought was analyzed by the virtualization deployment scheme of 5G core network, the architecture and scheme of 5G core network operation ＆amp; maintenance system construction were proposed, and suggestions on the organizational structure of 5G core network cloud-network integration operation ＆amp; maintenance were put forward, so as to provide reference for 5G core network cloud-network integration operation ＆amp; maintenance.